Effect of drying on the nutrient composition of Vernonia amygdalina leaves - I. Abdullahi, A. A. Aliero (Journal of Phytology, 2009)
Vernonia amygdalina (Bitter leaf) is a common and popular vegetable among the people of Nigeria used as a spice in many delicacies. In this study, the effect of solar, sun and oven drying methods on the proximate and mineral contents of its leaves was evaluated using standard analytical procedures. Drying increased significantly (P<0.05) the concentration of most of the organic constituents evaluated. The protein content was markedly enhanced by drying and it range from 1.31% in fresh sample to 5.30% in sun dried samples. A significant (P<0.05) increase in mineral content was observed upon drying except magnesium, whose concentration was found to be high (0.23 mg/100g) in fresh sample. The concentrations of Zn and Cd increased upon drying while, that Pb, Cr and Cu contents decreased. The results of this study suggest that drying improve the concentration of both organic and mineral constituents and solar drying method could be useful in preserving V. Ã‚Â amygdalina leaves in a more hygienic way and ensure its all-the-yearÃ¢â‚¬â€œround availability.